AB0521 Repeat Biopsy in Lupus Nephritis: A Single Center Analysis in Japan. (10th June 2014) - Tshilela, K.A.; Ikeuchi, H.; Hiromura, K.; Moxhizuki, K.; Kayakabe, K.; Sakurai, N.; Sakairi, T.; Kaneko, Y.; Maeshima, A.; Nojima, Y.
Abstract : Background: Repeat renal biopsy is occasionally performed in lupus nephritis (LN) patients in case of flare or worsening renal function. However, limited data are available regarding the histological changes of LN at repeat biopsy, especially by ISN/RPS 2003 classification. Objectives: In the present study, we sought to determine characteristics of patients who received repeat renal biopsy and to elucidate histological changes. Methods: We retrospectively analyzed LN patients with repeat renal biopsy among 150 biopsy-proven Japanese LN patients (19 males and 131 females with mean age of 36.8±13.8 years) at our department between 1976 and 2012. Renal histology was categorized by ISN/RPS 2003 classification. The chi-square test was used to compare the percentages between groups. Results: Nineteen patients (6 males and 13 females with mean age of 31.5±10.2 years) received repeat renal biopsy. The mean intervals between initial and repeat biopsy was 6.4±2.6 years. The reasons for the repeat biopsy were flare of LN in 18 patients and persistent proteinuria despite treatment in 1 patient. Among 79 patients who had class IV or III/IV+V (mixed type) at initial biopsy, 16 patients (20.3%) received repeat biopsy, whereas only 3 patients (4.2%) underwent it among patients with class II, III, or V at initial biopsy (p=0.003). A repeat biopsy was more frequently performed in male (31.6%) than in female (10.3%, p=0.008). The histological changes who underwent repeat biopsy was shown in Table. The class switches were observed in 7 patients (37%). Six patients changed to mixed type, and 1 patent with mixed type transformed to class III. In addition, chronic lesions (A/C or C by ISN/RPS) were increased from 4 patients at initial biopsy to 12 patients in repeat biopsy (p=0.020). Conclusions: Repeat biopsy was more frequently performed in male and in patients who had class IV or mixed type at initial biopsy. Approximately 40% patients showed class switches on repeat biopsy during a flare and most of them were a transition to mixed type. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4586